Urethral Lift as a Safe and Effective Procedure for Prostatic Hyplasia Population: A Systematic Review and Meta-Analysis - Jing, Jibo; Wu, Yuqing; Du, Mulong; Zhang, Nieke; Wang, Meiling; Xu, Bin; Chen, Ming (Frontiers in Surgery, 2020)
Background: Prostatic urethral lift (PUL) is a relatively new minimally invasive treatment procedure for benign prostatic hyperplasia (BPH). In order to analyze the sustainability of this new protocol, a systematic review and meta-analysis is performed based on the published articles. Methods: We performed a critical review according to the preferred reporting items for systematic review and meta-analysis (PRISMA) and MOOSE guidelines. A total of 818 published articles matched our search terms, and 11 studies met the inclusion criteria. Data of each follow-up time point (1, 3, 6, 12, and 24 months) were analyzed in terms of baseline characteristics and functional and sexual health outcomes. The merged means of each time point were calculated using R package meta and shown in the tendency plot. Results: A total of 1,443 patients who underwent PUL are available for the research. At 24 months, the changes of the three indicators are statistically significant (IPSS 9.40 points, p < 0.001; Qmax 3.39 ml/s, p < 0.001; QoL 1.99 points, p < 0.001) but were not as effective as TURP (from literature). The trend plot shows that, as time goes on, the effect of PUL tends to increase first and then weaken. Three items fitted a meaningful curve: IPSS (slope = −1.378 t = −12.395, p < 0.001), Qmax (slope = −1.382 t = −6.429, p < 0.001), and QoL (slope = −0.218, t = −10.058, p < 0.001). Fitted curves of SHIM and PVR are not statistically significant. The regression reveals that IPSS, Qmax, and QoL could be predicted after accepting PUL. Conclusion: PUL appears to be a safe and effective procedure in selected patients with BPH and can improve the symptoms of urinary tract obstruction. However, it is not as effective as TURP and shows no influence to the objective indicators like PVR.